﻿A study of the mealybug genus Planococcus Ferris, 1950 from China, with description of a new species (Hemiptera, Coccomorpha, Pseudococcidae) - Jiangtao Zhang; Jun Deng (ZooKeys, 2023)
A study of the mealybug genus Planococcus Ferris, 1950 (Hemiptera, Coccomorpha, Pseudococcidae) known from China is presented and 12 species are recognised. Of these, Planococcus camelliae Zhang, sp. nov. is described as new to science based on the morphology of the adult female, and P. bambusifolii (Takahashi, 1951) is recorded from China for the first time. Molecular analyses based on the mitochondrial gene cytochrome c oxidase subunit I (COI) of the new species and a key to species of the genus Planococcus in China are also given.